Plan de negocio para un laboratorio de larvicultura de camarón (Litopenaeus vannamei) en agua dulce en la ESPAM MFL - EP - Párraga Ganchozo, Jeniffer María (2019)
The purpose of this titling work was to develop a business plan that allows knowing the feasibility of investment for the creation of a freshwater shrimp larviculture laboratory in the ESPAM MFL - EP. The study aimed to analyze the market, technical and financial aspects, initially applying a survey to a sample of shrimp producers in the northern area of Manabí, the data collected allowed us to know aspects related to the requirements they demand at the time they acquire larvae, and the level of acceptance that the project has. Added to this, the technical study was carried out in which the larvae production capacity, their operational structure and the design of the plant with their respective spaces were determined; while in the financial evaluation, all the investment resources required for the implementation of the larviculture laboratory and its profitability indicators were specified, which determined that an investment of $60,040.86 is required to start the start-up of the laboratory during the first year; the profitability indicators show a VAN of $23,251.17, the TIR of 29%, a cost benefit ratio of $1.19 reflecting that for every dollar invested it is expected to generate 0.19 cents of profit, this result reflects that although the investment to be made is large, the project is profitable.